A posteriori diagnosis of DRESS syndrome induced by diazoxide in a patient with an insulinoma: a case report and review of the literature - Lassoued, Najoua; Alaya, Wafa; Arfa, Sondos; Korbi, Mouna; Lassoued, Ines; Amor, Soumaya Ben; Zaouali, Fatma; Farhat, Zayneb; Chelly, Jihen; Habib Sfar, Mohamed (Frontiers in Medicine, 2023)
The Drug Rash with Eosinophilia and Systemic Symptoms (DRESS) syndrome can be potentially life-threatening. The diagnosis is sometimes difficult since the clinical manifestations may be incomplete or non-specific. Insulinoma is a rare functioning neuroendocrine tumor (NET) of the pancreas. Medical therapy may be needed when surgery is contraindicated, delayed or refused. Diazoxide is widely used to control hypoglycemia in patients with insulinoma. We report a clinical case of an insulinoma in a 85-year-old patient treated with diazoxide with a fatal outcome due to a delayed diagnosis of a DRESS syndrome. This is the first case of DRESS syndrome reported after using diazoxide for insulinoma treatment in our knowledge.